Seasonal variability in ecosystem functioning across estuarine gradients: The role of sediment communities and ecosystem processes. (December 2020) - Mestdagh, Sebastiaan; Fang, Xiaoyu; Soetaert, Karline; Ysebaert, Tom; Moens, Tom; Van Colen, Carl
Abstract: Functional trait approaches advance the understanding of biodiversity–ecosystem function (BDEF) relationships and its control by the environmental context. Application of these insights into management remains constrained due to lack of evidence from real-world ecosystems that capture the natural spatial and temporal gradients at which biodiversity and environmental conditions operate. In this study we measured macrofauna community traits, ecosystem processes and abiotic properties at 9 locations during 4 months, spanning a wide gradient in sedimentary habitats and salinity in the Scheldt estuary, and quantified the (a)biotic contribution to sediment community oxygen consumption, as a measure of ecosystem function. We found that functional attributes of the macrofauna community and its effect on bio-irrigation can predict ecosystem function, but especially during the colder period of the year. This result highlights that generalizations about BDEF relationships, and biodiversity loss on ecosystem functions, are limited whenever this temporal component is not acknowledged. Graphical abstract: Image 1 Manuscript Highlights: Estuarine ecosystem functioning varies over space and time. Macrofauna community trait composition affects ecosystem processes and functioning. Higher relative contribution of macrofauna to ecosystem functioning in cold months.